Sequential shape-and-solder-directed self-assembly of functional microsystems - Zheng, Wei (National Academy of Sciences, 2004)
We demonstrate the fabrication of packaged microsystems that contain active semiconductor devices and passive components by using a directed self-assembly technique. The directed self-assembly is accomplished by combining geometrical shape recognition with site-specific binding involving liquid solder. Microfabricated components with matching complementary shapes, circuits, and liquid solder-coated areas were suspended in ethylene glycol and agitated by using a turbulent liquid flow to initiate the self-assembly. Microsystems were obtained by sequentially adding components of different types. Six hundred AlGaInP/GaAs light-emitting diode segments with a chip size of 200 μm were assembled onto device carriers with a yield of 100% in 2 min. Packaged light-emitting diodes formed with yields exceeding 97% as a result of two self-assembly steps in 4 min. This self-assembly procedure, based on geometrical shape recognition and subsequent binding to form mechanical and electrical connections, provides a high distinguishing power between different components and a route to nonrobotic parallel assembly of electrically functional hybrid microsystems in three dimensions.